2022
DOI: 10.1111/epi.17185
|View full text |Cite
|
Sign up to set email alerts
|

Surgical outcome of temporal plus epilepsy is improved by multilobar resection

Abstract: Objective: Temporal plus epilepsy (TPE) represents a rare type of epilepsy characterized by a complex epileptogenic zone including the temporal lobe and the close neighboring structures. We investigated whether the complete resection of temporal plus epileptogenic zone as defined through stereoelectroencephalography (SEEG) might improve seizure outcome in 38 patients with TPE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Figure 3 illustrates a very similar pattern of late recurrence for those who had ATL compared to the ET cohort, with the difference in risk between these two groups (higher for ET cohort) restricted to the early postsurgical period. Other studies have also reported late seizures in cohorts with a mixture of pathologies and/or surgeries 2 , 14 , 17 , 19 , 23 ; abnormal and/or normal pathology 15 ; lesional and/or nonlesional cases 24 , 25 , 26 , 27 , 28 , 29 ; focal cortical dysplasia 30 ; temporal lobe and "temporal plus" epilepsy 20 , 31 ; and ATL, ET, and amygdalohippocampectomy surgeries. 5 , 6 , 12 , 22 , 32 , 33 These findings favor hypotheses relating to causes of late seizure recurrence that apply broadly across these groups.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…Figure 3 illustrates a very similar pattern of late recurrence for those who had ATL compared to the ET cohort, with the difference in risk between these two groups (higher for ET cohort) restricted to the early postsurgical period. Other studies have also reported late seizures in cohorts with a mixture of pathologies and/or surgeries 2 , 14 , 17 , 19 , 23 ; abnormal and/or normal pathology 15 ; lesional and/or nonlesional cases 24 , 25 , 26 , 27 , 28 , 29 ; focal cortical dysplasia 30 ; temporal lobe and "temporal plus" epilepsy 20 , 31 ; and ATL, ET, and amygdalohippocampectomy surgeries. 5 , 6 , 12 , 22 , 32 , 33 These findings favor hypotheses relating to causes of late seizure recurrence that apply broadly across these groups.…”
Section: Discussionmentioning
confidence: 95%
“…Early studies by Rasmussen 18 described long‐term surgical outcome, noting 13% of "nontumoral" (median follow‐up = 12 years) and 6% of "tumoral" cases (median follow‐up = 8 years) experienced occasional seizures after at least 3 years free of seizures postsurgery. Late recurrences between 5 and 10 years postsurgery have been described in more recent cohorts 2,5,6,14,17,19,20 . There are few detailed data available relevant to the period after 10 postoperative years, although first recurrences after this time have been noted 2,14,21,22 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations